Intracellular vesicle acidification promotes maturation of infectious poliovirus particles. - Alexsia L Richards; William T Jackson (PLoS Pathogens, 2012)
The autophagic pathway acts as part of the immune response against a variety of pathogens. However, several pathogens subvert autophagic signaling to promote their own replication. In many cases it has been demonstrated that these pathogens inhibit or delay the degradative aspect of autophagy. Here, using poliovirus as a model virus, we report for the first time bona fide autophagic degradation occurring during infection with a virus whose replication is promoted by autophagy. We found that this degradation is not required to promote poliovirus replication. However, vesicular acidification, which in the case of autophagy precedes delivery of cargo to lysosomes, is required for normal levels of virus production. We show that blocking autophagosome formation inhibits viral RNA synthesis and subsequent steps in the virus cycle, while inhibiting vesicle acidification only inhibits the final maturation cleavage of virus particles. We suggest that particle assembly, genome encapsidation, and virion maturation may occur in a cellular compartment, and we propose the acidic mature autophagosome as a candidate vesicle. We discuss the implications of our findings in understanding the late stages of poliovirus replication, including the formation and maturation of virions and egress of infectious virus from cells.